Foreign Ownership and Transfer Pricing: The Moderating Role of Earnings Management - Amelia Oktrivina Siregar; Susilawati, Susilawati; Astuti, Shinta Budi; Gino, Dustin (Universitas Muhammadiyah Malang, 2026)
Purpose: This study examines the impact of foreign ownership and earnings management on transfer pricing decisions in Indonesian manufacturing firms, with a focus on earnings management as a moderating variable. Methodology/approach: Analyzing panel data from 25 basic industrial and chemical sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022 using EViews 13. Findings: Foreign ownership significantly increases transfer pricing, consistent with multinational tax optimization strategies. Earnings management shows no significant effect on transfer pricing and does not moderate the relationship between foreign ownership and transfer pricing, indicating these factors operate independently. Practical implications: Policymakers should enhance international tax coordination and implement stricter transparency measures to curb profit shifting. Firms are encouraged to strengthen governance frameworks to align transfer pricing policies with operational needs and regulatory compliance. Originality/value: The study contributes to the discourse on corporate tax strategies in emerging markets, particularly about tax-base depletion and profit shifting (BEPS) risks.